KEKERASAN EKONOMI DALAM RUMAH TANGGA: KAJIAN HUKUM PIDANA PASAL 9 UU 23 TAHUN 2004 - Kismala, Tria Putri; Rindiyanih, Rindiyanih; Perdana, Muhamad Bagas; Akbar, Sulaiman Kareemullah; Sebastian, Valerio (UIR Law Review, 2026)
Economic violence within domestic settings has increasingly been recognized as a critical yet underexplored dimension of domestic violence. While international frameworks, including the United Nations Declaration on the Elimination of Violence against Women (1993), acknowledge violence in both physical and non-physical forms, economic abuse remains insufficiently regulated and underreported in Indonesia. This conceptual article examines the nature, forms, and legal implications of economic domestic violence, conceptualizing it as a mechanism of coercive control and power imbalance within intimate relationships. Using normative legal analysis supported by international literature, the study evaluates the definition, structural impacts, and legal treatment of economic violence in Indonesian criminal law. Particular attention is given to Article 9 of Law No. 23 of 2004 on the Elimination of Domestic Violence (PDKRT Law), which criminalizes economic neglect and financial deprivation within households. The findings indicate that, despite explicit statutory recognition, economic violence remains underenforced due to limited legal awareness, socio-cultural norms that treat household financial matters as private, and substantial evidentiary difficulties in proving economic dependency and financial control. Enforcement is further constrained by narrow interpretative practices among law enforcement authorities. This article contributes to the literature by reconceptualizing economic domestic violence as an autonomous form of coercive control, critically assessing doctrinal and evidentiary limitations of Article 9 in practice, and highlighting the need for a victim-centered interpretative framework. The study concludes that strengthening legal literacy, judicial sensitivity, and public awareness is essential to enhance protection and ensure the effective implementation of domestic violence legislation in Indonesia.